Assisted migration outcomes for oak species and seed sources in southern Ontario, Canada - Pedlar, John H.; McKenney, Daniel W.; Sandvall, Kristen; Zurbrigg, Heather; McLaven, Kerry (Frontiers in Forests and Global Change, 2024)
Introduction Forest assisted migration has been proposed as a means to align tree populations with shifting climate habitats under climate change. Here we report on the growth and survival of oak species and seed sources at five assisted migration trials in southern Ontario – an important transition zone between boreal and temperate ecosystems. Methods Each trial featured one or more oak species – including red oak (Quercus rubra), white oak (Q. alba), burr oak (Q. macrocarpa), and swamp white oak (Q. bicolor) – and seed sources from Ontario, Pennsylvania, and/or Tennessee. The trials were measured for survival and height at between 7 and 13 years after planting. Results For several trials and species, southern seed sources performed nearly as well as local sources. However, southern seed sources of burr oak performed significantly worse than local sources at 2 trials in eastern Ontario. These outcomes may have been influenced by reduced quality of southern seed source planting stock at these trials. Discussion Our findings generally support previous work that suggests northward movements of seed sources of several hundred kilometers may be safe for assisted migration efforts involving broadleaf tree species. Notably, the trial sites were located at the northern range limits of two oak species in this study (Q. alba and Q. bicolor), suggesting the potential for modest range expansions in this boreal-temperate transition zone. These findings help forest managers to better understand potential assisted migration outcomes under climate change.